GNOSTIC HERITAGE IN PHILOSOPHICAL CONCEPTS OF THE CONTEMPORARY AGE AND TOTALITARIAN POLITICAL IDEOLOGIES OF THE 20TH CENTURY - Čizmar, Valentina (Political Review, 2026)
In this paper, the author starts from a genealogical consideration of the sources and differences between ancient and modern Gnosticism, as well as their crucial divergence from authentic Christian postulates (which relate primarily to the idea of salvation, the creation of the world, and the position of man in the world), in order to analyze the presence of the Gnostic heritage and ideas in some philosophical theories and modern political totalitarian ideologies. Those comparative analyses are based on the teachings of the political and philosophical thinkers Eric Voegelin and Hans Jonas, as well as other authors. Such political ideologies, which are opposed to realistic political theories, propagate the change of human reality within history into a reality without God, through various forms of manipulation, through new forms of “humanism”, through various ways of inhumane rule over people, by propagating revolutions, as well as through new forms of knowledge that can "transform" human nature, as well as act to erase their identity. The Gnostic interpretation of the world as a human prison created by the evil Demiurge, and pessimistic views on the alienation of man from nature, the world, and God, are met, on the other hand, with promises of human “salvation” through secret knowledge and the creation of a perfect and righteous world in the political-ideological sphere as well. Such an expression of Gnosticism belongs to political Gnosticism as well as social Gnosticism, which often manifest themselves as political extremism and end in utopia. Gnosticism as a kind of spiritual, religious and philosophical movement, developed with the emergence of Christianity, during the second and third centuries, tried to give answers to some spiritual questions which have sources also in Christianity. In the later centuries, modern Gnosticism become accepted in many modern totalitarian political ideology and ideas of modern and contemporary philosophies. In this paper the author starts from very obvious differences between Gnosticism and Orthodox Christian dogma when it is about the phenomenon of salvation, ideas about the real creation of this world and its Creator, humans’ position in such a world. The main gnostic idea differs from the biblical idea that this word is created by one perfect Being as it is God and claims that this imperfect world must be created by evil demiurge in which a human feels to be a stranger and tends to escape from it. Such an idea can be found in many Gospels, which are not a part of the Bible and that is part of gnostic literature. Salvation towards God and the transcendence world to gnostic one can be attained by the secret knowledge — gnosis, but for the few only. On the other hand, Gnosticism sees the world from a dualist perspective, human is apart from God, and human is thrown into the world as in prison, which we found in Heidegger philosophy, too and in Marx idea for transforming world through dialectic materialism. Such an ideas are also involved in many political ideologies that see salvation through political sphere. Christianity starts from the very different concept of world created by one perfect God, and the world and humans presented imago Dei (image of God), salvation is possible for all humankind, and primarily through faith (pistis) and not through sofia, as we see in one of the main works of Gnosticism as it is Pistis Sofia. The above-mentioned characteristics of ancient Gnosticism in the modern world took new form, so the idea of salvation is no longer coursed towards transcendent world, but towards immanence, to the historical sphere where humanity can change its reality through knowledge, science, political government, political ideology and various movement as it is communism, national-socialism, progressivism, as claims Voegelin. Actually, gnostic inheritance we can find not only in ancient world, but deeply rooted in political ideology of 20th century, especially in totalitarian political ideology, when we reflect on Voegelin’s main idea of the very strong influences of Gnosticism on modern political science, and its new meaning. On the model of Voegelin`s criticism of Marx ideas and communism, the author shows which gnostic paradigms are involved in the modern political ideologies. The author also analyzed the source of interpretation of the history of Western civilization through ancient Gnosticism (mediated by Eastern ideas) from the analysis of Hans Jonas. Such an interpretation of history can also be found existing in the modern European political structures that reject Christian roots. Gnostic ideas and thinking can be found not only in political theory, as it can be seen in Karl Schmits theory, or in the political ideology of national socialism, fascism, but also in Hegel’s, Heidegger’s, and Nietzsche’s philosophies, which propagated the world without God, new way of truth and transforming the human nature. Another line of gnostic influence and symbolism the author presented in modernity and its crisis, manifested through phenomena of secularization, atheism, avant-garde art and through new forms of spirituality and religion, as it is angelism, which Russian philosopher Epstein presented as form of minimal religion in the contemporary world that loses control over many realms such as economic, political, social spheres, and sphere of language, which are under the influence of technology as well.